KEMAMPUAN BAYAR, KEMAMPULABAAN DAN KONTRIBUSINYA DALAM MENOPANG PERMODALAN BANK PERKREDITAN RAKYAT - I Nyoman Nugraha Ardhana Putra; I Gede Mandra; I Dewa Gde Bisma; Sujadi Sujadi; Hery Susanto (Master of Management, Mataram University, 2020)
This Research aimed to analyze liquidity and profitability to the capital of Conventional Credit Society Bank. The associative method is using to analyze the problems that arise. The location of observation on conventional credit society bank (CSB) is in the province of West Nusa Tenggara, which has experienced the level of capital. The analysis used is path analysis. The results show liquidity has opposite effects indirectly through the profitability of capital. Those indicate the impact of the low liquidity but through to increase efficiency and the capital.Keywords:Liqiuidity, Profitability, Capital, Credit Society Bank (CSB)